PELAKSANAAN PROGRAM PEMBINAAN NARAPIDANA WANITA DI LEMBAGA PERMASYARAKATAN WANITA KLAS IIA SUNGGUMINASA - Mutfi Ramadhani; Abdul Mahsyar; Jaelan Usman (Department of Public Administration, Muhammadiyah University of Makassar, 2016)
This research aims to know the implementation of woman’s founding convict which are realized by a woman’s correctional in Sungguminasa, IIA Class. The kinds of this research are qualitative description by using a Primary data and Secondary data. This researching data is gotten by some methods like observation, documentation, and interview. Therefore,this data is analyzed by some steps they are Reduction, Display Data, Verification,and the last is Anticipatory. The result of this research shows that the implementation of woman’s founding convict which are realized by a woman’s correctional in Sungguminasa IIA Class is running well. Founding process is done by two methods, Personality’s founding and Autonomous founding. Personality’s founding includes religion consciousness and character building, then Autonomous founding includes skills and society’s effort.Keywords: Founding, Correctional, Woman Convicted Penelitian ini bertujuan mengetahui pelaksanaan program pembinaan narapidana wanita yang dilaksanakan oleh Lembaga Permasyarakatan Wanita Klas IIA Sungguminasa. Jenis penelitian ini adalah deskriptif kualitatif dengan sumber data primer dan data sekunder. Data diperoleh melalui observasi, dokumentasi dan wawancara. Data dianalisis secara reduction, displaydata dan verification kemudian dilakukan anticipatory. Hasil penelitian menunjukkan bahwa pelaksanaan program pembinaan narapidana wanita di Lapas Wanita Klas IIA Sungguminasa berjalan dengan baik. Proses pembinaan dilaksanakan melalui pembinaan kepribadian dan pembinaan kemandirian. Pembinaan kepribadian meliputi pembinaan kesadaran beragama dan pembinaan karakter. Sedangkan pembinaan kemandirian meliputi pembinaan keterampilan dan upaya pemasyarakatan. Kata kunci: pembinaan, lembaga permasyarakatan, narapidana wanita